Implementasi Standar Nasional Perpustakaan Perguruan Tinggi (SNP 010: 2011) di UIN Alauddin Makassar - Mardhaniah Mardhaniah (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2023)
This study aims to examine the implementation of the National Library Standards for Higher Education (SNP 010:2011) at UIN Alauddin Makassar library and to analyze the obstacles in the implementation of such National Library Standards. This is a descriptive research with qualitative approach. Data was collected through observation, interview and documentation techniques. The data collected was then analyzed qualitatively in three stages; data reduction, data presentation and conclusion drawing. The results showed that the seven standard indicators of SNP 010: 2011; collection standards, facilities and infrastructure, services, library staff, management, implementation, as well as information and communication technology at UIN Alauddin Makassar library have met the needs of libraries and users as national standards required. However, some obstacles found in the implementation of such SNP 010: 2011, thoser are: the limited number of library staff with a librarian education background, limited funds allocated to assist the implementation of human resource development activities, managerial continuity of UIN Alauddin Makassar Library was interrupted by the shift of senior librarians to functional lecturers, and the lack of computer facilities for users to browse library materials.